2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20183464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intralesional platelet rich plasma in chronic localized vitiligo

Abstract: <p class="abstract"><strong>Background:</strong> Vitiligo is a disease caused by destruction of melanocytes in lesional skin. It occurs worldwide in occurance of 0.1 to 2.0 percent. It is a multifactorial polygenic disease with complex pathogenesis. Several treatments, old and new are advocated for such patients. The first line of treatment includes topical corticosteroids and calcineurin inhibitors, and phototherapy (NBUVB, PUVA). The second line of treatment includes systemic corticosteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 3 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…It was also discovered that PRP therapy can induce and accelerate fibroblast proliferation and migration by up‐regulating cyclin E‐ and cyclin‐dependent kinase 4, which is essential in cell migration and proliferation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also discovered that PRP therapy can induce and accelerate fibroblast proliferation and migration by up‐regulating cyclin E‐ and cyclin‐dependent kinase 4, which is essential in cell migration and proliferation …”
Section: Discussionmentioning
confidence: 99%
“…27 It was also discovered that PRP therapy can induce and accelerate fibroblast proliferation and migration by up-regulating cyclin E-and cyclin-dependent kinase 4, which is essential in cell migration and proliferation. 12,13 In this research, the use of PRP was to increase the excimer laser impact and shorten the therapy length. This research showed that combining intradermal PRP injection with the excimer laser is a promising vitiligo therapy that can generate a substantial enhancement in stable, nonsegmental vitiligo in various body locations with minimal side effects and in a brief period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females outnumbering males in our study are in concordance to previous studies. [ 4 6 7 8 ] Increased social consequences in girls and women affected by vitiligo make them seek medical attention more than males. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…PRP could also increase the interaction of melanocytes with keratinocytes and stabilize the melanocytes. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%